Pengaruh Financial Literacy, Digital Payment Dan Financial Inclusion Terhadap Kinerja Keuangan pada UMKM Kuliner Pasar Sore Di Jalan Bhali Klaten - Rifqi Bernessa Putri; Dorothea Ririn Indriastuti (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This study aims to analyze the influence of financial literacy, digital payment and financial inclusion on financial performance in culinary UMKM Pasar sore on Jalan Bhali Klaten. Data collection in this study used questionnaires distributed to respondents. The sample in this study amounted to 85 traders at the Bhali Klaten afternoon market, with the type of sampling, namely saturated sampling. The analysis methods used in this study are descriptive analysis, multiple linear regression analysis, t-test, F-test (model accuracy test) and determination coefficient test (R2). The results of the t-test of the study showed that financial literacy had a significant effect on financial performance in culinary UMKM Pasar sore on Jalan Bhali Klaten with a p-value = 0.006 <0.05, digital payment had a significant effect on financial performance in culinary UMKM Pasar sore on Jalan Bhali Klaten with a p-value = 0.000 <0.05, and financial inclusion had a significant effect on financial performance in culinary UMKM Pasar sore on Jalan Bhali Klaten with a p-value = 0.018 <0.05